High confidence and demand for hepatitis E vaccine during an outbreak in Bentiu, South Sudan: A qualitative study. - Aybüke Koyuncu; Kinya Vincent Asilaza; John Rumunu; Joseph Wamala; Priscillah Gitahi; Zelie Antier; Jetske Duncker; Patrick Nkemenang; Primitive Gakima; Melat Haile; Etienne Gignoux; Manuel Albela; et al. (PLOS Global Public Health)
In 2021 in response to an outbreak of hepatitis E in Bentiu internally displaced persons camp the South Sudanese Ministry of Health with support from Médecins Sans Frontières implemented the first-ever mass reactive vaccination campaign with HEV239 (Hecolin; Innovax, Xiamen, China). We conducted qualitative research to assess knowledge, attitudes, and practices related to hepatitis E and the hepatitis E vaccine. We conducted 8 focus group discussions (FGDs) with community leaders, the general population of vaccine-eligible adults, vaccine-eligible pregnant women (vaccinated and non-vaccinated), and healthcare workers. FGDs were separate by gender and were audio recorded, transcribed, and translated to English. Two coders used inductive thematic analysis to organize emergent themes. Data were collected in November 2022. Most participants had experiences with hepatitis E (e.g., infected themselves or knowing someone that had been infected) and viewed hepatitis E as a dangerous disease. Participants believed children, pregnant women, and older persons were the highest risk groups and frequently made requests for additional hepatitis E vaccination campaigns and expanded eligibility criteria for vaccination. Knowledge of the negative impacts of hepatitis E and trusted relationships with the organizations offering the vaccine were key facilitators of vaccine acceptance. The primary barriers to vaccination were practical issues related to being away from the camp during the campaign or not knowing about the campaign, but participants shared that some in the community were unvaccinated due to fears about injections, social pressure, misinformation, and concerns about why some groups were eligible for vaccination and not others (e.g., young children). Personal experiences with hepatitis E illness, perceived severity of illness, and confidence in organizations recommending the vaccine were drivers of high demand for hepatitis E vaccines in the first-ever use of the vaccine in an outbreak setting. Addressing practical issues related to population mobility can improve coverage in future campaigns.